2010
DOI: 10.1093/toxsci/kfq140
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Maternal Effects on Valproic Acid Teratogenesis in C57BL/6J and DBA/2J Mice

Abstract: Valproic acid (VPA) is used worldwide to treat epilepsy, migraine headaches, and bipolar disorder. However, VPA is teratogenic and in utero exposure can lead to congenital malformations. Using inbred C57BL/6J (B6) and DBA/2J (D2) mice, we asked whether genetic variation could play a role in susceptibility to VPA teratogenesis. Whereas B6 fetuses were more susceptible than D2 fetuses to digit and vertebral malformations, D2 fetuses were more susceptible to rib malformations. In a reciprocal cross between B6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…4, 18, 19 However, there are contradictory reports regarding the effects of VPA on apoptotic death of NPCs at developmentally critical periods. 28, 32 Studies have shown that the reduced (Go et al 28 ) or increased (Kataoka et al 32 ) apoptotic deaths of NPCs by VPA treatment underlie neurodevelopmental defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4, 18, 19 However, there are contradictory reports regarding the effects of VPA on apoptotic death of NPCs at developmentally critical periods. 28, 32 Studies have shown that the reduced (Go et al 28 ) or increased (Kataoka et al 32 ) apoptotic deaths of NPCs by VPA treatment underlie neurodevelopmental defects.…”
Section: Discussionmentioning
confidence: 99%
“…17 Several studies have proposed that HDAC inhibition by VPA is closely related to teratogenesis in vertebrate embryos. 4, 18, 19 A growing body of evidence suggests that VPA has neuroprotective and neurotrophic effects on neural progenitor cells (NPCs) and neurons, apart from its function as an AED. It promotes neuroplasticity, neurogenesis and cell survival.…”
mentioning
confidence: 99%
“…26 The teratogenic effects of VPA could involve altered micro RNAs expression. 27,28 Various forms of VPA, and more importantly, newer generation of AEDs like lamotrigine, topiramate, and gabapentin show signals for either congenital jaw or oral malformation. 29 About half a century ago, thalidomide was widely prescribed to pregnant women as a sedative and anti-nauseant but it proved to be teratogenic, causing multiple birth defects particularly limb malformations.…”
Section: 17mentioning
confidence: 99%
“…A study by Downing et al (2010) also found differences in the teratogenic response of C57BL/6J and DBA/2J mice to a single dose of valproic acid given on GD 9, i.e., while C57BL/6J fetuses were more susceptible than DBA/2J fetuses to induction of digit (fused or missing digits) and vertebral anomalies (fused, missing and asymmetrical arches and centra), the latter strain was more susceptible than the former mouse strain for the induction of rib anomalies (fused, missing, bifurcated, and wavy/ bulbous ribs). Since the authors did not determine the number of somite pairs, inter-strain differences IBRAHIM CHAHOUD and FRANCISCO J.R. PAUMGARTTEN of developmental stages at the time of treatment cannot be ruled out as contributing factors for these differences in susceptibility to VPA-induced teratogenicity.…”
Section: Table III (Continuation)mentioning
confidence: 99%
“…Moreover, it is known that, in polytocous mammals, the stage of development of individual embryos varies within the litter and between litters at a same gestational age. Nonetheless, a strain-dependent difference in the development of embryos of the same age has seldom been considered as a possible cause for inter-strain differences in susceptibility to teratogens (Linval et al 1982, Moreno and Epstein 1987, Biddle 1988, Juriloff et al 1991, Biddle et al 1993, Hall et al 1997, Datta et al 2008, Downing et al 2010. Along this line, it should be mentioned that a comparative study of the embryo development in four mouse strains (NMRI, BALB/cJ, DBA/2J and C57BL/6J) revealed remarkable differences among them in somite counts on defined gestation times (GD) between GD9 and GD12 (Thiel et al 1993).…”
mentioning
confidence: 99%